Researches regarding the influence of the some technological elements on water use efficiency in maize from Crisurilor Plain - Borza, Ioana; Domuţa, Cristian (Acta Agraria Debreceniensis, 2013)
Plain and the influence of the hybrid, plant density, crop rotation, nutrient supply, weeds and irrigation on water use efficiency were studied. Choosing of the hybrid with the best water use efficiency is very important because a hybrid from 500–600 FAO group (Fundulea 376) in unirrigated conditions and a hybrid from FAO group over 600 (Fundulea 365) obtained the biggest water use efficiency; the hybrid Fundulea 365 obtained the highest irrigation water use efficiency, 20.1 kg yield gain 1 mm-1 irrigation water. One of the most known hybrid in the area is Turda super and the highest water use efficiency was obtained using the plant density of 55 000 plants/ha in unirrigated variant and 70 000 plants/ha in irrigated variant. The highest irrigation water use efficiency, 20.7 kg yield gain 1 mm-1, was obtained at 70 000 plants ha-1. In maize monoculture was obtained the lowest values of the water use efficiency in unirrigated and irrigated variant: in the wheat-maize crop rotation the values were higher than in maize monoculture and in the wheat-maize-soybean were registered the highest values. The same situation was registered regarding the irrigation water use efficiency. Farm manure (30 t ha-1) and especially manure (30 t ha-1) +chemical fertilizers (N90P45) determined a higher values of the water use efficiency in comparison with the control. In the variant with organic + mineral fertilization was registered the higher value (19.4 kg yield gain mm-1) of the irrigation water use efficiency. Water use efficiency was much lower in the variant with weeds in comparison with the variant without the weeds; the differences were of 69% in unirrigated variant and of 64% in irrigated variant, very significant statistically. Irrigation water use efficiency from variant with weeds was lower than the value registered in the variant without weeds; the difference (68%) was very significant statistically. In average in period 1976–2012, the irrigation determined the increasing in water use efficiency with 22%, 19.4 kg mm-1 vs. 15.8 kg mm-1, but not in all the years caused the irrigation increasing in water use efficiency in comparison with unirrigated maize. The results research emphasized the need of the optimization for technology elements studied and a better water use efficiency will be obtained.